Green roofs as a nature-based solution for improving urban sustainability: Progress and perspectives - Mihalakakou, Giouli; Souliotis, Manolis; Papadaki, Maria; Menounou, Penelope; Dimopoulos, Panayotis; Kolokotsa, Dionysia; Paravantis, John A.; Tsangrassoulis, Aris; Panaras, Giorgos; Giannakopoulos, Evangelos; Papaefthimiou, Spiros (Renewable & sustainable energy reviews, 2023)
Green roofs are artificial ecosystems that provide a nature-based solution to environmental challenges such as climate change and the urban heat island. Green roofs aid in the conservation of both cooling and heating energy; deposition of particulates and mitigation of air pollution; control of runoff and water pollution; promotion of biodiversity; and provision of aesthetic and health benefits. This research is a holistic review of the green roof literature and provides a global perspective of the subject with a classification of modelling studies; and an extensive review of contributions to energy conservation, carbon sequestration, mitigation of air pollutants, runoff control; and urban noise reduction. The review covers the system's thermal performance modelling through several methodologies; experimental studies; parametric studies to assess the impact of various parameters on the system's energy efficiency using several configuration parameters such as leaf area, foliage height and density, plant coverage, roof insulation, soil thickness, and irrigation; energy benefits; and environmental benefits including air pollutants mitigation, carbon sequestration, runoff control and urban noise reduction. Finally, review was complemented with a life cycle assessment study of green roofs, which examined the extraction of raw materials, manufacturing and construction, transportation, and disposal. Green roofs can reduce the cooling load by up to 70%, decrease the indoor temperature achieving an indoor air temperature reduction up to 15 °C, and provide a significant improvement of thermal comfort conditions. The environmental benefits of green roofs were focused on decreasing pollutants concentrations (e.g. PM2.5, PM10, O3, NO2), sequestering carbon and reducing urban noise. •A nature-based approach of green roofs is provided.•A critical perspective as regards green roofs improving urban sustainability is adopted.•Green roof systems may reduce the cooling load up to 70%.•Coupling green roof systems with life cycle assessment.•There is significant potential for energy savings for green roof systems.